Acute vascular effects of atorvastatin in hypertensive men: a pilot study. (October 2013) - Saluveer, Ott; Bergh, Niklas; Grote, Ludger; Andersson, Ove; Hrafnkelsdóttir, Thórdis J.; Widgren, Bengt R.
Abstract Objectives. Statins have multiple pleiotropic effects that are independent of their cholesterol-lowering properties including rapid improvement of endothelial function in vitro. Hypertension is characterized by endothelial dysfunction and we hypothesized that a single-dose of atorvastatin may have an acute effect on vascular function. Design. Endothelium-dependent vasodilation (EDV) and endothelium-independent vasodilation were assessed with venous occlusion plethysmography during intra-arterial infusion of acetylcholine (ACH) and sodium nitroprusside (SNP), respectively, in 13 hypertensive men after wash-out from antihypertensive medication. Vasoconstrictive responses were evaluated in response to angiotensin II (Ang II) infusion. The protocol was repeated 1 h after 80 mg oral atorvastatin (ATV; Lipitor®). Results. ATV treatment significantly increased baseline forearm blood flow from 3.38 (0.27) to 4.31 (0.35) ml/min/100 ml tissue (p < 0.05). ATV did not affect ACH-induced EDV. Forearm vascular resistance in response to SNP was significantly lowered by ATV (p < 0.05). Vasoconstriction in response to Ang II was significantly inhibited by ATV treatment (p = 0.005). Conclusions. The observed acute statin effects in hypertension appear to be endothelium-independent and related to vascular smooth muscle cell function. These actions may in part contribute to the beneficial pleiotropic effects of statin therapy even in the acute in vivo setting.